Vallejo Yesterdays: 20 Years Ago from the Chronicle Files - Vallejo News Chronicle (Vallejo News Chronicle)
20 Years Ago Today: The Board of Governors of the California Maritime Academy yesterday passed resolutions accepting land at Morrow Cove in Vallejo for the new school's proposed home base. Capbain Robert Henderson, chairman of the board, is expected to come here within a few days to accept the deed to the land donated by local interests.